Penerapan Terapi Murattal Al-Qur’an Terhadap Tingkat Skala Halusinasi Pendengaran pada Pasien Skizofrenia di RSJD Dr. RM. Soedjarwadi Provinsi Jawa Tengah - Masyriatul Munawaroh; Tri Susilowati; Wahyu Reknoningsih (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
The prevalence of schizophrenia mental disorder reaches 1.7% of a thousand Indonesian population with a total of 400,000 sufferers. Schizophrenia has an impact on sufferers, one of which is hallucinations. Sufferers listen to murattal Al-Qur'an as a way to reduce hallucinations. To find out the results of applying Al-Qur'an murattal therapy to the level of auditory hallucination scale in schizophrenic patients at RSJD Dr. RM. Soedjarwadi Central Java Province. This research includes descriptive research with case studies. The results before implementing the murattal Al-Qur'an level of the auditory hallucination scale on Mr. M is moderate with an AHRS score of 16 and Mr. R is heavy with an AHRS score of 23. After implementing the murattal Al-Qur'an the level of the auditory hallucination scale on Mr. M is mild with an AHRS score of 9 and Mr. R is moderate with an AHRS score of 15. In the application that has been carried out, there are developments in 2 respondents, namely experiencing a decrease in the level of hallucinations of sufferers after listening to murattal Al-Qur'an. There is a comparison of development between the levels of the hallucination scale after and before listening to the murattal Al-Qur'an.